KEPEMIMPINAN ETIS DAN PERILAKU KERJA INOVATIF - Roni Aswad; Donal Devi Amdanata (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2023)
The research method employed a literature review (library research), collecting data from various literature related to the research topic. This study explores the relationship between ethical leadership and innovative work behavior, considering the increasing recognition of ethical leadership as a distinct leadership style. Based on Social Exchange Theory, this research investigates the impact of ethical leadership on employees' innovative work behavior, emphasizing the holistic perspective of ethical leadership. The findings contribute valuable insights to management studies, specifically in leadership, organizational behavior, and human resource management. Additionally, the research emphasizes the role of ethical leadership in shaping positive and innovative work behaviors among employees, providing guidance for organizational management to design strategies preventing behaviors that may undermine innovative work behavior.